Federated States of Micronesia : Technical Assistance Report-Government Finance Statistics Mission (October 25-November 2, 2021). (IMF Staff Country Reports; Country Report, 2022)
A virtual technical assistance (TA) mission supported by the IMF's Asia and Pacific Department (APD) was conducted by the IMF Statistics Department (STA) and the Pacific Financial Technical Assistance Centre (PFTAC) during October 25 - November 2, 2021. The mission assisted the Department of Resources and Development (DoRD), National Statistics Office (NSO) improving the compilation and dissemination of Government Finance statistics (GFS) and Public Sector Debt Statistics (PSDS) according to the Government Finance Statistics Manual 2014 (GFSM2014) and the Public-Sector Debt Statistics Guide 2011 (PSDSG 2011). The mission was conducted under the Data for Decisions (D4D) trust fund,1 a multi-donor initiative aimed at strengthening the quality of national statistical outputs to better support economic policy making in low-and lower-middle income countries and the PFTAC GFS capacity development project.